Experimental and Theoretical Studies of the Colloidal Stability of Nanoparticles−A General Interpretation Based on Stability Maps - Segets, Doris; Marczak, Renata; Schäfer, Stefan; Paula, Carolin; Gnichwitz, Jan-Frederik; Hirsch, Andreas; Peukert, Wolfgang (Acs Nano, 2011)
The current work addresses the understanding of the stabilization of nanoparticles in suspension. Specifically, we study ZnO in ethanol for which the Influence of particle size and reactant ratio as well as surface coverage on colloidal stability in dependence of the purification progress was investigated. The results revealed that the well-known zeta-potential determines not only the colloidal stability but also the surface coverage of acetate groups bound to the particle surface. The acetate groups act as molecular spacers between the nanoparticles and prevent agglomeration. Next to DLVO calculations based on the theory of Derjaguin, Landau, Verwey and Overbeek using a core shell model we find that the stability is better understood in terms of dimensionless numbers which represent attractive forces as well as electrostatic repulsion, steric effects, transport properties, and particle concentration. Evaluating the colloidal stability in dependence of time by means of UV-vis absorption measurements a stability map for ZnO is derived. From this map it becomes clear that the dimensionless steric contribution to colloidal stability scales with a stability parameter including dimensionless repulsion and attraction as well as particle concentration and diffusivity of the particles according to a power law with an exponent of -0.5. Finally, we show that our approach is valid for other stabilizing molecules like cationic dendrons and is generally applicable for a wide range of other material systems within the limitations of vanishing van der Weals forces in refractive index matched situations, vanishing zeta-potential and systems without a stabilizing shell around the particle surface.
Keywords: nanoparticles; stabilization; particle size; electrostatic; repulsion

Influence of annealing temperature and measurement ambient on TFTs based on gas phase synthesized ZnO nanoparticles - Walther, Sabine; Schäfer, Stefan; Jank, M. P. M.; Thiem, H.; Peukert, Wolfgang; Frey, Lothar; Ryssel, Heiner (Microelectronic Engineering, 2010)
In this paper, we report on the applicability of gas phase synthesized ZnO nanoparticles for printed electronics. Electrical characteristics of thin film transistors with an active layer based on ZnO nanoparticle dispersions are presented. A low charge carrier mobility and a low Ion/Ioff ratio are found for the devices when measured in nitrogen atmosphere. The mobility is limited by the rough interface between semiconductor and dielectric. Additional electrical measurements in dry air reveal a dependency of the Ion/Ioff ratio on surface states of the ZnO particles. It is shown that adsorption of oxygen on ZnO nanoparticles leads to improved transistor characteristics.
Keywords: Nanoparticle; Printable electronics; Thin film transistor; Zinc oxide

Self-alignment of zinc oxide nanorods into a 3D-smectic phase - Schäfer, Stefan; Srikantharajah, Rubitha; Klaumünzer, Martin; Lobaz, Volodymyr; Voigt, Michael; Peukert, Wolfgang (Thin Solid Films, 2014)
We focus on thin films from ZnO nanorod dispersions in order to generate a high lateral order and a dense space filling structure applicable e. g. in printed optoelectronic devices. Highly stable dispersions with a solid content of up to 60 wt.% in ethanol were prepared using trioxadecanoic acid as stabilizer. With the dispersions we prepared thin films on substrates with a 3D-smectic phase in lateral dimension of cm2 and thicknesses from below 100 nm up to 1 μm. We show how the concentration of the initial solid content is influencing the formation of domains in our films and discuss the self-assembly process into ordered structures.

Stabilization mechanism of ZnO quantum dots - Peukert, Wolfgang; Marczak, Renata; Schäfer, Stefan; Segets, Doris (Nanotechnology 2010: Advanced Materials, CNTs, Particles, Films and Composites - 2010 NSTI Nanotechnology Conference and Expo, NSTI-Nanotech 2010, 2010)
The current work addresses the understanding of the stabilization of small ZnO quantum dots in ethanolic suspension. Thereby different degrees of purification were investigated. The results revealed that not only the well-known ζ-potential as a representative for the surface charge determines the colloidal stability but also the surface coverage of acetate groups bound to the particle surface. Those acetate groups act as molecular spacers between the nanoparticles and prevent agglomeration. Regarding DLVO-calculations using a core-shell model, not only the height of the maximum but also the depth of the primary minimum has to be considered to see if a colloidal suspension is stable or not.
Keywords: Core-shell model; Purification; Quantum dot; Stability; ZnO